2020
DOI: 10.3390/microorganisms8101469
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Productivity and Fecal Microbiotas of Sows in Commercial Farms

Abstract: Sow productivity, that is, the number of weaned piglets per sow per year, depends on their health status. The gut microbiota is considered a crucial factor in the health of pigs and may affect sow productivity. In the present study, we aimed to investigate the relationship between productivity and the fecal microbiotas of sows in different farms. Feces of sows were collected from 18 farms (10 samples/farm). A total of 90 fecal samples of high-reproductive performance farms were labeled as group H, and 90 fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Interestingly, the significant difference in alpha diversity disappeared, but significant difference was observed in beta diversity between HP and LP groups on d 110 of gestation. This was in keeping with the results in Uryu et al ( 12 ) who explored the relationship between sow productive capacities and the fecal microbiota in different farms. However, Shao et al ( 40 ) reported that alpha diversity and beta diversity both differed between sows with high- and low-reproductive performance during late gestation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, the significant difference in alpha diversity disappeared, but significant difference was observed in beta diversity between HP and LP groups on d 110 of gestation. This was in keeping with the results in Uryu et al ( 12 ) who explored the relationship between sow productive capacities and the fecal microbiota in different farms. However, Shao et al ( 40 ) reported that alpha diversity and beta diversity both differed between sows with high- and low-reproductive performance during late gestation.…”
Section: Discussionsupporting
confidence: 89%
“…However, Shao et al ( 40 ) reported that alpha diversity and beta diversity both differed between sows with high- and low-reproductive performance during late gestation. It might suggest that the beta diversity, not alpha diversity, was a critical factor to evaluate the effect of gut microbiota on sow reproductive performance ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Butyrate is the main end product of some non-pathogenic species of the genus Clostridium (72-74), which contribute to preserve a healthy intestinal microecology through the control of the growth of pathogenic microbes (75-77), while living in harmony with commensal members of the families Bacteroidaceae, Enterococcaceae, and Lactobacillaceae (77). In a previous study, the relative abundance of SCFA-producing bacteria and the concentrations of acetate, propionate and butyrate were significantly higher among fecal samples from highreproductive performance farms than among those from lowreproductive performance farms (78). Streptomycin treatment depleted butyrate-producing clostridia from the murine gut, decreased butyrate levels, and increased the population of pathogens like Salmonella enterica serovar Typhimurium (79).…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, early-life nutritional intervention has significant potential in reducing the risk of gastrointestinal infections in piglets. Furthermore, it promotes growth performance in piglets ( 12 ). Tan et al ( 13 ) reported that pigs with high-feed efficiency exhibit large numbers of beneficial bacteria in their gut.…”
Section: Introductionmentioning
confidence: 99%